1994
DOI: 10.1159/000112080
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones and the Central Nervous System

Abstract: Thyroid hormones have a significant influence on the development and maturation of the central nervous system. Among their actions, T3 and T4 have effects on the differentiation of various cell types in the rat brain and cerebellum as well as on the process of myelination. Recently, several investigators have shown effects of thyroid hormones on myelin protein gene expression. Thyroid hormones seem to have a regulatory role with regard to life span. Hyperthyroid animals appear to have a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 45 publications
4
38
0
2
Order By: Relevance
“…In developing mammals (including humans), a deficiency or excess of thyroid hormone (TH) in the developing brain during the fetal and neonatal periods can lead to morphologic and functional abnormalities (15)(16)(17)(18). The most severe form of TH deficiency in human fetus and neonate is the syndrome of cretinism.…”
Section: Discussionmentioning
confidence: 99%
“…In developing mammals (including humans), a deficiency or excess of thyroid hormone (TH) in the developing brain during the fetal and neonatal periods can lead to morphologic and functional abnormalities (15)(16)(17)(18). The most severe form of TH deficiency in human fetus and neonate is the syndrome of cretinism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the central nervous system, thyroid hormone deficiency results in a generalized delay in brain growth, while thyroid hormone excess accelerates neurogenic development (2,3,43). In both cases, the orderly progression of neuronal maturation through stages of proliferation, migration, differentiation, neurite outgrowth, synaptogenesis, and myelination is disrupted, with profound and irreversible consequences with respect to function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the levels of thyroid hormones required for development and the timing of their appearance are critical; exposure of the embryo to excessive levels of these compounds is highly detrimental. In mammals, this can result in fetal malformations, growth retardation, craniosynostosis, and abnormal brain development that is manifested by learning disabilities and mental retardation (3)(4)(5)(6)(7)(8). In amphibia, premature exposure to exogenous thyroid hormones results in uncoordinated development that inevitably results in larval death (9).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it is more than likely that the observed BPA effects, combined with numerous biologically linked mechanisms, also occur in vivo, with the notion that in vivo, TRβ expression is restricted to specific ontogenetic states and is highly tissue specific (Bradley et al, 1994). Altogether, this idea is consonant with results from animal models that have shown that hypothyroidism during critical periods of development causes a variety of abnormalities in the central nervous system (Pasquini and Adamo, 1994;Martinez-Galan et al, 1997;Simorangkir et al, 1997), and that TRα and TRβ can compensate for each other's hypofunction. Finally, it should be noted that a growing body of evidence exists to show that BPA and other EDs increase intracellular reactive oxygen species and generate oxidative stress conditions in mitochondria and endoplasmic reticulum (Huc et al, 2012;Babu et al, 2013).…”
Section: Further Considerationsmentioning
confidence: 81%